2017
DOI: 10.1098/rspb.2017.1083
|View full text |Cite
|
Sign up to set email alerts
|

Nest prospecting brown-headed cowbirds ‘parasitize’ social information when the value of personal information is lacking

Abstract: Brood parasites face considerable cognitive challenges in locating and selecting host nests for their young. Here, we test whether female brown-headed cowbirds, , could use information acquired from observing the nest prospecting patterns of conspecifics to influence their own patterns of nest selection. In laboratory-based experiments, we created a disparity in the amount of personal information females had about the quality of nests. Females with less personal information about the quality of two nests spent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Our results indicate that social information (chemical and/or structural cues) on the silk of earlier searchers can allow a male to find a female efficiently even when access to personal information (volatile sex pheromone) is minimized. This is consistent with the prediction that animals should use social information when personal information is out of date, unreliable or expensive to obtain [22][23][24]27]. Male black widows apparently move upwind to seek personal information (figure 3c), but when weak or absent wind makes detection of a pheromone source difficult or impossible, they can nonetheless find females by following the silk trails of rivals ( figures 2b,d and 3d).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results indicate that social information (chemical and/or structural cues) on the silk of earlier searchers can allow a male to find a female efficiently even when access to personal information (volatile sex pheromone) is minimized. This is consistent with the prediction that animals should use social information when personal information is out of date, unreliable or expensive to obtain [22][23][24]27]. Male black widows apparently move upwind to seek personal information (figure 3c), but when weak or absent wind makes detection of a pheromone source difficult or impossible, they can nonetheless find females by following the silk trails of rivals ( figures 2b,d and 3d).…”
Section: Discussionsupporting
confidence: 83%
“…How and when animals use personal and social information to make mating-related decisions will depend on conditions including temperature/weather, physical structure of the habitat, and ecological variables such as predation risk and the spatio-temporal distribution of conspecifics. These factors will affect the fitness benefit and feasibility of acquiring and using social compared to personal information, so information use is expected to be contextdependent [22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Further tests of the idea that superior female spatial ability is associated with search for host nests could be performed in large enclosures (e.g. White et al 2017) that more closely resemble the spatial scale at which females search for host nests. Superior performance by male brown-headed cowbirds in breeding condition on the touchscreen spatial task is puzzling but the domain of this sex difference could be further examined by varying the kind of spatial task presented on the touchscreen, in more naturalistic foraging tasks or in tests of memory for the spatial location of females.…”
Section: Spatialmentioning
confidence: 99%
“…Successful reproduction is a product of a lifetime of interactions with the world, and thus documenting the effect of any one aspect of cognition on reproductive success can be less than straightforward. For example, the efficacy of cognitive abilities may vary by context, being useful in some environments but not others (Cole et al, 2012), cognitive skills may interact positively or negatively with each other (Kawecki, 2003), and alternative cognitive strategies for dealing with specific challenges may exist (White et al, 2017). Cole et al (2012) provide an illuminating example of a complex interaction between cognition and reproductive success.…”
Section: Introductionmentioning
confidence: 99%
“…White and colleagues have studied the cognitive processes that female cowbirds use when prospecting for nests in aviaries (Davies & White, 2018;White, 2019;White et al, 2007aWhite et al, , b, 2009White et al, 2017). This work has revealed that females are extremely adept at finding nests, and once found, select among nests based on size, pattern, and the number of eggs present.…”
Section: Introductionmentioning
confidence: 99%